(untitled) (Journal of actual problems of jurisprudence, 2021)
In the theory of criminal law, special attention has always been paid to social norms enforced by the coercive power of the state. Despite the availability and accuracy of sentencing issues, the article talks about the regulation of criminal legislation, about the presence of still unresolved parties to the issue requiring its clarification and revision. Since the restoration of social justice as the goal of criminal punishment proceeds from the principle of justice – one of the most important principles of criminal law, affecting the restoration of social justice of punishment, based on several opinions and practical data, taking into account that an important place in the theory of criminal law of the Republic of Kazakhstan and other countries occupy punishment and its goals, as one of the goals of punishment the author considered comprehensively analyzing the application of restoration of social justice in relation to punishment in the form of imprisonment. The attention that arose is explained by the special place of criminal punishment in the system of legal measures to combat crime. An important aspect of punishment is the correct understanding and formulation of the purpose of criminal punishment. The author emphasizes that when creating the goal of punishment, it is advisable to consider the process of combating crime as a negative part of society, not only through the impact on crime, but also in the conditions that give rise to this crime. Key words: criminal law, crime, punishment, purpose of punishment, imprisonment, social justice.